2017
DOI: 10.4236/ojpm.2017.74006
|View full text |Cite
|
Sign up to set email alerts
|

The Practice of Exclusive Breastfeeding and Its Sociodemographic Determinants amongst Nursing Mothers at a Tertiary Health Care Institution in South East, Nigeria

Abstract: Background: Breastfeeding is a natural and critical act that provides nutrients and energy for the infant and young child; and through a public health intervention such as exclusive breastfeeding, it improves the survival rates of the infant. Objective: To determine the breastfeeding practices and the sociodemographic determinants of exclusive breastfeeding amongst nursing mothers present at the Imo state university teaching hospital Orlu. Methods: A cross sectional analytical study design was used that includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 17 publications
(15 reference statements)
1
2
0
Order By: Relevance
“…Mothers who had no education at all or only primary education were less likely to feed breast milk exclusively for the first 6 months. This finding is in agreement with previous studies reported in Ethiopia [46][47][48], Malaysia [49], and Nigeria [34,50]. Maternal and child health care services such as postnatal and antenatal care, were risk factors of exclusive breastfeeding; i.e., mothers who received professional postnatal and antenatal care were more likely to exclusively breastfeed their infant.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Mothers who had no education at all or only primary education were less likely to feed breast milk exclusively for the first 6 months. This finding is in agreement with previous studies reported in Ethiopia [46][47][48], Malaysia [49], and Nigeria [34,50]. Maternal and child health care services such as postnatal and antenatal care, were risk factors of exclusive breastfeeding; i.e., mothers who received professional postnatal and antenatal care were more likely to exclusively breastfeed their infant.…”
Section: Discussionsupporting
confidence: 92%
“…The practice of exclusive breastfeeding was congruent with a similar previous study conducted in Uganda [26] which reported 46%, and in East Gojjam zone, Amhara regional state [29] reported 50.10%. In contrast, a study done in a Rajkot district of India 62% [30], Dilla Zuria District, Gedeo Zone 57.60% [31], Enderta woreda, of Tigray regional, state 70.20% [32], Ghana 64% [33], and Nigeria 56.60% [34] reported a higher proportion of exclusive breastfeeding. These differences might be the variation in health service utilization, culture, socioeconomic status of the study participants', taboos about breastfeeding (colostrum) and methodological approaches used in the studies [39].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation